Intelligent Computer Techniques in Applied Electromagnetics - Wiak, Slawomir; Krawczyk, Andrzej; Dolezel, Ivo (Studies in Computational Intelligence, 2008)
This book contains selected papers presented at the International Symposium on Electromagnetic Fields in Mechatronics, Electrical and Electronic Engineering ISEF'07 which was held in Prague, Czech Republic, September 13-15, 2007. It is the tradition of ISEF meetings that they try to tangle quite a vast area of computational and applied electromagnetics. The methods of evaluation and control of electromagnetic field which base on Artificial Intelligence (AI) constitute the core of majority of the papers presented during ISEF'07 conference. The papers selected to this volume are linked with the AI theory and methodology, i.e. they do not use the numerical method automatically but they attempt to contribute some new AI tools to computer modelling. The papers selected into three chapters represent the following topics: Algorithms and Intelligent Computer Methods, Computer Methods and Engineering Software, Applications of Computer Methods. The first chapter is focused on information techniques. The reader may find here such problems as multi-agent algorithms, neural networks, genetic algorithms, wavelet transformation, paralleling of computation problems, monitoring and others. In second chapter one can find papers which deal with numerical modelling of such devices as high voltage power lines, actuators, NMR and induction tomography, adaptive plasma, electrochemical machining and others. The third group consists of the papers dealing with the application of advanced algorithms and methods to selected engineering problems, dealing with optimization of a Drive System, Combined Electromagnetic and Thermal Analysis by means of approximate methods, combined Finite Element Method (FEM) and Finite Volume Method (FVM), algorithms based on stochastic methods and others.